Neonatal lupus erythematosus presenting with rash, thrombocytopenia compounded by cytomegalovirus colonisation: a diagnostic dilemma. Issue 6 (11th June 2020) - Agrawal, Gopal; Varghese, Bincy; Balde, Manish; Wazir, Sanjay
Abstract : Neonatal lupus erythematosus (NLE) should be considered when a newborn develops atrioventricular heart block along with the presence of autoantibodies to Sjogren's syndrome autoantigens in the maternal serum. NLE can also present with features such as cutaneous lesions, hepatic dysfunction or haematological abnormalities. Differential diagnosis usually includes congenital infections as there is a significant overlap of symptoms with NLE. We report a case of NLE who had multiorgan involvement with macular erythematous skin lesions present at birth, and on investigation was found to have cytomegalovirus (CMV) infection. The diagnostic dilemma was whether to consider this infection as symptomatic or just colonisation. In the infant described, the absence of end organ damage specific to CMV infection (hearing loss, intracranial calcifications, retinitis, brain involvement) made a diagnosis of symptomatic CMV unlikely.